Zakat Sebagai Pesan Dakwah - Hamdan Dauly (LPPM IAIN Sorong, 2018)
If alms is managed and benefited well, it has potency of strategies to equality of nation economic at Indonesia. But, the problem occurs in Islam society that knowledge, awareness, and experience toward command to do alms still weakly. Moreover, the formulating of alms are still used the expert of alms formulating for the last some decades, so that it is not suitable used for arranging alms in modern society for present day. Preaching concept based on wisdom, the best instruction and the excellent ideas, it can be developed become approach and methodology of alms development that is effective, efficient and touching the heart of humanity. The socialization of alms whether it is about its law, its wisdom, method of excavation and its collecting, management and its beneficial until the existing of changing as to change the mustahiq status to be muzakki is an important part of the alms movement and social matter to return the knowledge of alms in society. Thus, the goal of alms is the equality of economic, problem solving of labor force and unemployment, serving of healthy for the poor society, and then to overcome the neglected children and orphan be able accomplished with well.